An American soldier in World War I - Browne, George, 1894-; Snead, David L. (David Lindsey) (Lincoln : University of Nebraska Press, 2006)
"George "Brownie" Browne was a twenty-three-year-old civil engineer in Waterbury, Connecticut, when the United States entered the Great War in 1917. He enlisted almost immediately and served in the American Expeditionary Forces until his discharge in 1919. An American Soldier in World War I is an edited collection of more than one hundred letters that Browne wrote to his fiancee, Martha "Marty" Johnson, describing his experiences during World War I as part of the famed 42nd, or Rainbow, Division."--Jacket
Mobilization and training in the United States -- From the States to a quiet sector in France -- Training and action in a quiet sector -- Initiation to combat: champagne and the Battle of Ourcq River -- Rest and the Battle of Saint-Mihiel -- The Meuse-Argonne Offensive and the end of the war.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Browne, George, -- 1894- -- Correspondence; United States. -- Army. -- Engineer Regiment, 117th.; Browne, George, -- 1894- -- Correspondence; Browne, George, -- 1894-; United States. -- Army. -- Engineer Regiment, 117th; World War, 1914-1918 -- Campaigns -- France; World War, 1914-1918 -- Personal narratives, American; Military engineers -- United States -- Correspondence; Guerre mondiale, 1914-1918 -- Campagnes et batailles -- France; Ingénieurs militaires -- États-Unis -- Correspondance; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Military -- World War I; HISTORY -- Modern -- 20th Century; Military campaigns; Military engineers; France; United States; Soldat; Weltkrieg; Frankreich; USA; 1914 - 1918; autobiographies (literary works); Personal narratives; Autobiographies; Personal narratives -- American; Personal correspondence; Autobiographies; Personal narratives; Autobiographies; Récits personnels